2013
DOI: 10.1111/mec.12414
|View full text |Cite
|
Sign up to set email alerts
|

First evidence of cryptic species diversity and significant population structure in a widespread freshwater nematode morphospecies (Tobrilus gracilis)

Abstract: Free-living nematodes are ubiquitous and highly abundant in terrestrial and aquatic environments, where they sustain ecosystem functioning by mineralization processes and nutrient cycling. Nevertheless, very little is known about their true diversity and intraspecific population structure. Recent molecular studies on marine nematodes indicated cryptic diversity and strong genetic differentiation of distinct populations, but for freshwater nematode species, analogous studies are lacking. Here, we present the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 90 publications
(146 reference statements)
1
31
0
Order By: Relevance
“…Discovery of crypsis is particularly important within groups of morphologically simple invertebrates with few taxonomically diagnostic characters. Recent examples of groups in which cryptic species have been found include cnidarians (Schuchert, 2014), marine nematodes (Derycke et al, 2005), freshwater nematodes (Ristau et al, 2013), and parasitic nematodes (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Discovery of crypsis is particularly important within groups of morphologically simple invertebrates with few taxonomically diagnostic characters. Recent examples of groups in which cryptic species have been found include cnidarians (Schuchert, 2014), marine nematodes (Derycke et al, 2005), freshwater nematodes (Ristau et al, 2013), and parasitic nematodes (Tan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among the best lead stories for the media are discoveries of new, invasive or other enigmatic species (for example, parasitic living lampreys, or the notion of the "highest DNA barcode" from a moth from the top of Germany's highest mountain). Several scientific publications have resulted from the first phase of GBOL and the Barcoding Fauna Bavarica project, including, for example, the demonstration of extreme levels (up to 16.7% p-distance) of cryptic diversity in the centipede Stenotaenia linearis (Wesener et al 2015) or a widespread freshwater nematode morphospecies (Ristau et al 2013). Analyzing more than 400 species of true bugs, other colleagues showed that DNA barcodes are highly effective in distinguishing over 90% of Heteroptera species (Raupach et al 2014), and a similar high level of identification success was observed in neuropterids and Lepidoptera (Hausmann et al 2011a(Hausmann et al , 2011b.…”
Section: Highlights/discoveries Of New Speciesmentioning
confidence: 99%
“…Geographically, M. curvatum has been reported from six continents in both tropical and temperate climates. Judging from these reports, either this species is an extreme generalist, adapted to a multitude of environments and plant hosts, or M. curvatum as recorded in the literature is actually a composite of morphologically similar but genetically distinct lineages, possibly cryptic species (Fontaneto et al, 2008;Nadler and De Le on, 2011;Ristau et al, 2013;Palomares-Rius et al, 2014).…”
mentioning
confidence: 99%